INVESTIGATING STUDENTS’ BURNOUT AND ENGAGEMENT IN EFL CLASSROOM: A MIXED-METHOD STUDY - Dasya Restiana Valerin; Amalul Umam; Rinta Nariza Imansani; Alan Jaelani (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2026)
Students’ burnout has become an important issue in EFL classrooms because it may affect students’ engagement and academic performance during English learning activities. Therefore, this study aimed to investigate students’ burnout and engagement in EFL classrooms using an explanatory sequential mixed-method design. Quantitative data were collected through questionnaires and analyzed using Mann-Whitney U test and Pearson correlation analysis. Qualitative data were obtained through semi-structured interviews with six students and analyzed using thematic analysis. The findings revealed a significant difference between male and female students’ burnout and engagement levels. In addition, the Pearson correlation analysis showed a significant negative relationship between students’ burnout and academic English performance. The qualitative findings identified three major factors contributing to students’ burnout, namely environmental, psychological, and individual factors. Among these factors, psychological factors emerged as the most influential contributor to students’ burnout experiences. Overall, the findings suggest that burnout may negatively affect students’ engagement and academic achievement in EFL classrooms.